How Fly Me to the Moon expresses meaning: A pragmastylistic view - Loeis, Jhonson; Lubis, Heri Setiawan; Harianja, Alvernod; Dachi, Paulus; Rangkuti, Rahmadsyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates how “Fly Me to the Moon,” written by Bart Howard and popularized by Frank Sinatra, constructs meaning through a pragmastylistic lens. While often discussed for its historical and cultural significance, the song’s linguistic features—especially its use of speech acts, implicature, metaphor, repetition, and parallelism—remain underexplored. By integrating insights from pragmatics and stylistics, this research examines how these elements interact to enhance the song’s emotional resonance and poetic expression. The findings contribute to a broader understanding of how language and style work together to create meaning in song lyrics, demonstrating the artistic potential of everyday linguistic tools.